Spatial and temporal transformations of resource‐producing subjects of the Russian Federation in 2012–2021 - Yu. V. Petrov; B. I. Kochurov (Юг России: экология, развитие, 2024)
Allocation of spatial and temporal transformations in resource‐producing subjects of the Russian Federation for the decade 2012–2021 based on the comparison of tax revenue materials with budget execution data.The materials of the study were information from the Federal Tax Service of the Russian Federation, Form 1, regulatory legal acts. The values for 2 federal taxes were used as incoming tax revenues: corporate income tax and personal income tax. Research methods were: comparative, computational and cartographic.During the period under review, 13 territories were assigned at least once to the group with high raw materials specialisation, for which negative features of response to external challenges are inherent:‐ there was not a single subject of the Russian Federation in which the growth of budget expenditures with a proportional and large increase in tax revenues was observed;‐ only in 2018, was an increase in budget expenditures noted for all territories with a simultaneous increase in tax revenues from mining;‐ only in 4 subjects of the Russian Federation budget did expenditures continuously increased, while some members of the group had budget expenditures reduced against the background of the growth of raw material tax revenues.During the period under review, high economic uncertainty and the accompanying transformation in regional policy were revealed, resulting in a change in the number and composition of participants in resourceproducing subjects of the Russian Federation.